Balancing Sustainable Global Mining Business with Social Good: The Rio Tinto Alcan Venture in Northern Australia - Pearson, Cecil; Liu, Yi; Daff, S. (Society for Global Business & Economic Development (SGBED), 2011)
Global mining corporations have contributed significantly to Austrlian economic development and national infrastructure, and it is touted they are one of the few organisations delivering training and employment opportunities for Indigenous people in the remote mining areas. Persistently advanced is globalisation will enable these marginalised people to substaintially reduce their socio economic disadvantage, but the evidence is they continue to have unsuitable housing, poorer health status and lesser life expectancy, while greater access to wealth is linked to substance abuse, which manifests as heightened violence, greater incarceration, and more suicides than experienced in the non Indigenous population. In this paper is reported findings from a four year study with Indigenous people, who have exercised an opportunity for engagement in an educational programme and employment in a mainstream job in a remote Australian mining operation. The results demonstrate allowing global mining corporations to operate in remote regions of Australia may lead to a resurgence of interest in Indigenous employment, but an expectation their representation in the mining workforce will increase and/or their social disadvantage will be significantly reduced is worthy of revisitation.